Impact of Lactobacillus casei BL23 on the Host Transcriptome, Growth and Disease Resistance in Larval Zebrafish - Qin, Chubin; Xie, Yadong; Wang, Yibing; Li, Shuning; Ran, Chao; He, Suxu; Zhou, Zhigang (Frontiers in Physiology, 2018)
In this study, zebrafish were treated with Lactobacillus strains as probiotics from hatching to puberty, and the effect of treatment with L. casei BL23 on the development and immunity response of the host was investigated. Genes that were differentially expressed (DEGs) in the overall body and intestine were detected at 14 days post fertilization (dpf) and 35 dpf, respectively, using whole transcriptome sequencing (mRNAseq). We showed that zebrafish raised by continuous immersion with L. casei BL23 showed a higher final body weight at 14 dpf (P < 0.05), and 35 dpf (P < 0.01). DEGs between L. casei BL23 treatment and control group at 14 dpf were involved in myogenesis, cell adhesion, transcription regulation and DNA-binding and activator. At 35 dpf, 369 genes were differentially expressed in the intestine after treatment with L. casei BL23, which were involved in such categories as signaling, secretion, motor proteins, oxidoreductase and iron, tight junctions, lipid metabolism, growth regulation, proteases and humoral and cellular effectors. KEGG analysis showed DEGs to be involved in such pathways as those associated with tight junctions and the PPAR signal pathway. RT-qPCR analysis showed that expression of insulin-like growth factors-I (igf1), peroxisome proliferator activated receptors-α (ppar-α) and -β (ppar-β), Vitamin D receptor-α (vdr-α), and retinoic acid receptor-γ (rar-γ) was up-regulated in fish treated with L. casei BL23 at 35 dpf. After 35 days of treatment, the mortality rate in L. casei BL23 treated group was lower than the control after challenge with A. hydrophila (P < 0.05), and the pro-inflammatory cytokine il-1β, anti-inflammatory cytokine il-10 and complement component 3a (c3a) showed more expression in L. casei BL23 group at 8h after challenge, 24 h after challenge, or both.. Together, these data suggest that specific Lactobacillus probiotic strains can accelerate the development profile and enhance immunity in zebrafish, which supports the rationale of early administration of probiotics in aquaculture.